Theoretical Calculations of the Seasonal and Solar Activity Variations for Ionospheric Collision Frequency and Debye Length over Baghdad City - Ali Hussein Ni'ma (Al-Mustansiriyah Journal of Science)
In this study, two important ionospheric factors have been calculated, the collision frequency of electron and Deby length for a height range from 80 Km to a height approaching the maximum height of the F2 region of the ionosphere above the Earth's surface. Both above factors have been calculated for two different levels of solar activity and for two seasons (winter and summer). Also, six months were adopted for every level of solar activity and season. The estimation of collision frequency of electron is depends on the contribution of neutral constituents and ions. Three neutral atmospheric gases have been adopted to calculate the collision frequency, Molecular and atomic oxygen O2 and O respectively and molecular nitrogen N2, as well as the singly charged ions were taken into account in calculation.